(untitled) (Castilla. Estudios de Literatura, 2020)
In recent decades literary scholars have referred to the ideas contained in three related texts circulated at the time of the première of El sí de las niñas in 1806. Versions of these brief unpublished documents are held in the Biblioteca Nacional de España, two of them copied by Moratín himself. The present article transcribes the texts, reproducing a previously unused, more complete manuscript of one of them, located in London’s British Library. The annotated transcriptions are accompanied by critical analysis assessing their validity and evaluating their interest in relation to original audiences of the play in 1806.